Alcanivorax sediminis sp. nov., isolated from deep-sea sediment of the Pacific Ocean. Issue 7 (3rd July 2020) - Liao, Xianzhi; Lai, Qiliang; Yang, Junpeng; Dong, Chunming; Li, Dengfeng; Shao, Zongze
Abstract : A taxonomic study was carried out on strain PA15-N-34 T, which was isolated from deep-sea sediment of Pacific Ocean. The bacterium was Gram-stain-positive, oxidase- and catalase-positive and rod-shaped. Growth was observed at salinity of 0–15.0% NaCl and at temperatures of 10–45 °C. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain PA15-N-34 T belonged to the genus Alcanivorax, with the highest sequence similarity to Alcanivorax profundi MTEO17 T (97.7 %), followed by Alcanivorax nanhaiticus 19 m-6 T (97.3 %) and 12 other species of the genus Alcanivorax (93.4 %–97.0 %). The average nucleotide identity and DNA–DNA hybridization values between strain PA15-N-34 T and type strains of the genus Alcanivorax were 71.46–81.78% and 18.7–25.2 %, respectively. The principal fatty acids (>10 %) were summed feature 8 (C18 : 1 ω 7 c and/or C18 : 1 ω 6 c ; 31.2 %), C16 : 0 (25.0 %) and summed feature 3 (14.6 %). The DNA G+C content was 57.15 mol%. The polar lipids were phosphatidylethanolamine, phosphatidylglycerol, diphosphatidylglycerol, four unidentified aminolipids and three unidentified lipids. The novel strain can be differentiated from its closest type strain by a negative test for urease and the presence of diphosphatidylglycerol and aminolipid. The combined genotypic and phenotypic data show that strain PA15-N-34 T represents a novel species within the genus Alcanivorax, for which the name Alcanivorax sediminis sp. nov. is proposed, with the type strain PA15-N-34 T (=MCCC 1A14738 T =KCTC 72163 T ).